The child welfare challenge: policy, practice and research - Pecora, Peter J. (Modern application of social work, 2009)
Purpose and goals of child welfare -- Key child welfare legislation and other policies -- A conceptual framework for child and family-centered services -- Economic security for families with children -- Child maltreatment types, rates, and reporting procedures -- Child protective services -- Family-based services -- Family foster care -- Family reunification and kinship care -- Transition and independent living services -- Adoption and adoption services -- Residential group care and intensive treatment alternatives -- Organizational requisites and challenges to effective child welfare services